Whatsapp Group as a Communication Technology in Higher Education Internationalization - Widya Pujarama; Arif Budi Prasetya (Jurnal Ilmu Komunikasi, 2018)
Individual adaptability towards communication media in Higher Education institutions as organizational entities could be reviewed from social semiotic perspective. Following Kress, social semiotic is a theory focuses on how semiotic resources in a varied social situation and locations become meaningful signs regulating human interaction. The theory was adapted in this research to translate patterns and activities of communication occurred in internationalization initiatives recorded in Whatsapp Group PSIK FISIP Universitas Brawijaya, as an artefact of communication. Non-participant observation was conducted towards series of 7 months conversations on Whatsapp Group as sequences of communicative act, and then analysed using Van Leeuwen’s four Dimension of Semiotic Analysis. Results indicate that there were distinction between administrative staff and lecturers with added function in the way they post their messages, indexing “doers” and “thinkers” that further conforming to their offline interaction standpoints when collaborating for internationalization activities.